PENGARUH SELEKSI DAN PENEMPATAN PEGAWAI TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI BMT FAMILIER KOTA GAJAH LAMPUNG TENGAH - SUWARTO SUWARTO; SITI MUSLYA SITI MUSLYA (Derivatif : Jurnal Manajemen, 2015)
The existence of human resources in a company is very important because they they also play a role in the survival of a company, Human resources is huge potential asset for the level of productivity of a company. BMT Familier Kota Gajah Central Lampung by observation placement accuracy is not in accordance with the educational background, conformity ability and suitability of expertise. Formulation of the problem in this study is whether the recruitment and staffing affect the employee productivityat BMT Familier Kota Gajah Central Lampung in 2015.The purpose of this study was to determine the effect reception and staffing to employees productivityworking in BMT Familier Lampung Central Lampung in 2015. Type of research is descriptive qualitative research procedure that produces descriptive data based on the results of a quantitative analysis of the study variables. The technique of collecting data using interviews, documentation and questionnaires using a questionnaire. The analysis tool is to use data quality analysis and multiple linear regression analysis.In conclusion, the results of the analysis of recruitment has a significant impact on employee productivity. Placement of employees has a significant impact on employee productivity. Seeing these results it can be said that the independent variables are positive and significant impact on employee performance. Keywords: Admission, Placement, Employee Productivity.